The notebooks of Joseph Joubert : a selection - Joubert, Joseph, 1754-1824; Auster, Paul, 1947-2024 (New York : New York Review Books, 2005)
Joseph Joubert was een Franse filosoof die o.a. contacten had met Diderot en Chateaubriand.
Keywords: Joubert, Joseph, -- 1754-1824 -- Notebooks, sketchbooks, etc